DAKWAH DI BALIK PERANG: STRATEGI KOMUNIKASI ISLAM DALAM MENGHADAPI PERANG SALIB - Asmar, Aulia Artika; Zahra, Annisa; Dalimunthe, Muhammad Zulfahmi Azmi; Ajizah, Nur; Baiti, Nur; Anwar, Rini Fitria; Yazid, Sadewa; Windari, Sri (Cahaya Ilmu Bangsa Institute, 2025)
This article examines the Crusades as a period not only of military conflict but also of significant Islamic communication and dakwah strategies. While the Crusades are often seen through the lens of religious warfare between Islam and Christianity, this study explores the ways in which Islamic leaders and scholars employed various communication methods to mobilize support, maintain morale, and articulate their position. Using a library research method, this study analyzes historical sources to identify key strategies of dakwah and communication used by Muslims during the Crusades. The findings reveal that these strategies played a crucial role in shaping Muslim responses to the Crusades and had a lasting impact on Islamic identity and solidarity. This article aims to provide a deeper understanding of the role of dakwah in the context of historical conflict and its relevance to contemporary Islamic communication.